Environmental and economic trade-off-based approaches towards urban household waste and crop straw disposal for biogas power generation project -a case study from China. (15th October 2021) - Xu, Jiuping; Liu, Zhiwen; Dai, Jingqi
Abstract: Development and utilization of biomass waste for energy, especially urban household waste and crop straw waste, has garnered global attention. To enable the clean recycling of biomass waste, this study designed a biogas power generation project with a single/mixed raw material input, and established a multi-objective dynamic programming model under an uncertain environment to compare the economic and environmental differences between biogas production and landfill/incineration. Fuzzy membership function was used to deal with the uncertainty problems of daily crop straw yield and methane content in produced biogas. The proposed project and model were then utilized for an actual case area, and scenario analyses were conducted. Through the sensitivity analysis of the profitability expectations and straw input levels, it was found that single-feedstock anaerobic digestion could improve economic benefits while mixed-feedstock anaerobic digestion was more beneficial to reduce carbon emissions. This revealed a mechanism that the project's objectives of environmental protection and economic development could be regulated through the raw material procurement scheme for urban household waste and crop straw, and the allocation plan of processing capacity for anaerobic digestion with single/mixed raw materials. The results showed that the proposed methodology was efficient for the disposal of the biomass waste, and carbon emissions were only about 30% of that achieve via landfill/incineration. The economic benefits included the achievement of 6.74 × 1 0 6 CNY per year. Compared with previous studies, this study reported the successful development of a practical and effective biogas power generation project for treating biomass waste. Effective management methods have been proposed to optimize the processes of anaerobic digestion and power generation to ensure stable project operations.